Sibutramina: validação de metodologia e avaliação biofarmacotécnica - Diefenbach, Isabel Cristina Fração (2007)
Sibutramine is therapeutically classified as an anorexigen, being recommended for obesity treatment and reduction of body weight, combined with diet and exercises. Its expected activity is the weight loss through inhibiting serotonin and norepinephrine reuptakes. By dual inhibition, sibutramine reduces body weight, then reducing food ingestion through intensification of post-prandial satisfaction. The drug is commercially available as industrialized capsules and compounded capsules. There are no official monographs up to this moment, to control the quality of this drug in its pharmaceutical forms. In the present work, methods for the quantification and dissolution evaluation of the drug in industrialized capsules were developed and validated. Comparative studies among some commercially formulations were also performed. UV spectrophotometry and liquid chromatography methods were developed and validated for quantitative determination, and showed linearity, precision and accuracy. The selected conditions for the dissolution test were 500 mL of 0.1 M HCl as medium, using basket for capsules, with rotation speed of 75 rpm. The comparative study presented that products not showed quality deviations.